STRUCTURAL POSITION OF THE ZILAIR FORMATION IN THE SOUTHERN URAL - Kazantseva T.T.; Kazantsev Yu.V.; Kamaletdinov M.A. (My University, 2004)
The Zilair Synclinorium is one of the largest structural units on the western slope of the southern Ural. In the west, its northern and southern parts join the Bashkir Anticlinorium and the Ural Foredeep, respectively. In the east, the synclinorium borders with the Uraltau structure. The identification of the Zilair Formation as an autonomous allochthon is undoubtedly an incorrect idea that is not consistent with the factual data on regional stratigraphy. This indicates again that the studied folded region is in need of comprehensive geological studies, because interpretations based on occasional observations may lead to confusions.